Understanding the Relationship Marketing and the Guanxi within the Taiwanese Auto Parts Industry - Hsieh, Ming-Hsun (2009)
The aim of this research is to investigate the importance of relationship marketing as well as the guanxi concept in the auto parts industry in Taiwan. The analysis of the auto parts industry was been conducted initially. Following the chapter, the researcher tried to understand the factors from both constructs through a literature review. The differences between the two concepts have also been analysed. By concentrating on the auto parts firms which try to maintain a long-term relationship with their clients, this research conducted both quantitative and qualitative research methods to generate a comprehensive result. By using surveys to simplify the response from interviewees, the general scenario of relationship marketing would be revealed. By using semi-structured interviews, researchers can further analyse the relation between relationship marketing, guanxi concept literatures and auto parts firms. A survey of both suppliers and buyers has been conducted to generate a comprehensive result toward the research object.